Implementação e desimplementação do custeio baseado em atividades (ABC): o caso CTBC - Barra Neto, André (2007)
This dissertation presents the trajectory of the Activity Based Cost System - ABC in the Company of Telephones of Central Brazil - CTBC. Demonstrating as it was the process of choice and implementation of this system, its use and the reasons by which the same was disactivated. Thus, the study focus the ABC Cost System, its relevance and its incompatibility with the CTBC, a company where the fixed costs are significant and also has multiple services that use shared assets and resources. To the development of the work, the descriptive research was used as method, thus were made surveys in physical and magnetic ways of materials and archives of the time, as also interviews with employees of the CTBC. The main consideration that was possible to evidence was that, as more than 80% of the CTBC resources are fixed costs and with a high degree of sharing between the activities, it had one high degree of allocation subjectivity on the activities costs, what caused great distortions in the gotten costs, what turned impracticable the use of the ABC for the CTBC.